Young people in aged care: trends in the use of aged care services by younger Australians, 2008–2016. Issue 8 (10th April 2021) - Inacio, Maria C.; Khadka, Jyoti; Lang, Catherine; Harrison, Stephanie; Crotty, Maria; Whitehead, Craig; Wesselingh, Steve
Abstract: Purpose : To determine incidence rate of aged care service use between 2008–2009 and 2015–2016 by younger Australians and the yearly rate of change. Material and methods: A population-based epidemiological study was conducted using publicly available datasets from the Australian Institute of Health and Welfare and Australian Bureau of Statistics. The incidence of service utilization by younger people (<65 year) and per 10, 000 citizens 0–49, 50–54, 55–59, and 60–64 years old per year was estimated. Negative binomial regression models were used to estimate incidence rate ratios. Results: Between 2008–2009 and 2015–2016 the number of younger people accessing services increased for home care services by 103.2% and transition care by 131.9% but decreased for permanent residential care by 0.4%, and respite care by 2.4%. Permanent residential care incidence use decreased for the overall population (incidence rate ratio = 0.98, p  < 0.001) and in those 55–59 years old (incidence rate ratio = 0.97, p  < 0.001) and for respite care incidence use decreased in those 0–49 years old (incidence rate ratio = 0.93, p  = 0.001). The incidence use of home care increased in the overall group (incidence rate ratio = 1.04, p  < 0.001) and in those 50–54 (1.08, p  < 0.001) and in those 55–59 years old (incidence rate ratio = 1.03, p  < 0.001). The use of transition care services increased significantly in all age groups (overall incidence rate ratio = 1.09, p  < 0.001). Conclusions: The overall use of permanent residential care has decreased along with the use of respite in the youngest people, and the use of home and transition care services have increased. Efforts to keep young people out of residential aged care may have redirected them to home care services. Implications for rehabilitation: The number of young people (<65 years old) with disability using aged cares services in Australia has increased significantly between 2008–2009 and 2015–2016. The overall use of permanent residential care has decreased along with the use of respite care, and the use of home and transition care services have increased, which should be encouraged. Development of targeted rehabilitation support programs to support young people with disability housed in residential aged care may help to better cater their care needs. Development of transition pathways to shift young people with disability to appropriate support programs may help to reduce the number of younger people with disability in aged care services.